Tinjauan Penggunaan Uang Elektronik Dalam Perspektif Hukum Syariah - Munawir Munawir; Mahbub Mahbub (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
The community's need for micro-payment methods that can make payment processes faster and more efficient and secure with less expensive administration than using credit cards and debit cards is to use electronic money. The purpose of this research is to find out whether the concept of using electronic money is in accordance with PBI Number 11/12 / PBI / 2009 as well as the implementation of the use of electronic money in the perspective of sharia law. The method used is the library research method. The results of this study indicate that the concept of electronic money that has been implemented is in accordance with PBI Number 11/12 / PBI / 2009. The use of electronic money issued by banks uses the Sharf contract as the main contract and is also equipped with the Ijarah and Wakalah contracts. The Sharf contract is implemented in cash exchange for electronic money which includes both online and offline transactions. The ijarah contract is applied in service / lease services, in which case the operator can get a fee from the service. The wakalah contract is applied in cooperation with other parties so that the other party receives compensation from the issuer for the services of its representatives. Based on the results of this research, it can be said that the use of electronic money can be implemented in accordance with syarriah law.